2020
DOI: 10.1136/bmjqs-2019-010734
|View full text |Cite
|
Sign up to set email alerts
|

Changing hospital organisational culture for improved patient outcomes: developing and implementing the leadership saves lives intervention

Abstract: BackgroundLeadership Saves Lives (LSL) was a prospective, mixed methods intervention to promote positive change in organisational culture across 10 diverse hospitals in the USA and reduce mortality for patients with acute myocardial infarction (AMI). Despite the potential impact of complex interventions such as LSL, descriptions in the peer-reviewed literature often lack the detail required to allow adoption and adaptation of interventions or synthesis of evidence across studies. Accordingly, here we present t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 26 publications
0
18
0
2
Order By: Relevance
“…We found it imperative that a clinician in a leadership role, such as a chief nursing officer or medical director, is engaged at the outset to shepherd the tool's implementation and champion its use. 31 This leader's tasks included setting the expectation for the use of predictive analytics monitoring in clinical care, mobilizing resources, and Fig. 1 The predictive monitor.…”
Section: To Maximize Buy-in Engagement At All Levels Is Importantmentioning
confidence: 99%
“…We found it imperative that a clinician in a leadership role, such as a chief nursing officer or medical director, is engaged at the outset to shepherd the tool's implementation and champion its use. 31 This leader's tasks included setting the expectation for the use of predictive analytics monitoring in clinical care, mobilizing resources, and Fig. 1 The predictive monitor.…”
Section: To Maximize Buy-in Engagement At All Levels Is Importantmentioning
confidence: 99%
“…The data also showed that in the Egyptian context, a top bottom approach is appropriate to drive a change; meaning that engaging senior physicians and department directors is essential for any change in the practices of younger physicians. Trust in the perceptions of senior practitioners have been shown to be powerful reasons for the inappropriate prescription of antibiotics in several countries in the world [ 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…System redesign to assist in the eradication of global health inequities clearly requires the successful recruitment and retention of appropriate healthcare workers, which is an international problem in rural, remote, and very remote contexts (Hines et al, 2020b ). It is possible, however, to use system-wide interventions to change important elements such as organizational culture and leadership (Linnander et al, 2020 ). For changes to be effective, responsive, and sustained, decisions regarding system reform should be informed by the genuine and meaningful contributions of all stakeholders including patients (Rabideau, 2020 ) and Community Health Workers (Schurer et al, 2020a , 2020b ).…”
Section: Foundational Research Questionsmentioning
confidence: 99%
“…Process: Engaging What is the ideal organization of health services and systems for eradicating global health inequities? •Systems must provide specialist but essential services during global pandemics •Ongoing monitoring and evaluation could guide the redesign of services and systems •Recruitment and retention of appropriately trained and skilled staff is critical Ademuyiwa et al ( 2020 ), Lazarus et al ( 2020a , ( 2020b ), Binagwaho and Mathewos ( 2020a ), Phillips et al ( 2020 ), Binagwaho et al ( 2020a , 2020b ), Binagwaho and Mathewos ( 2020b ), Carey and Binagwaho ( 2020a ), Binagwaho ( 2020 ), Henley ( 2020 ), Schurer et al ( 2020 ), Semrau et al ( 2020 ), Hines et al ( 2020b ), Linnander et al ( 2020 ), Rabideau ( 2020 ), Schurer et al ( 2020a , 2020b ) III. Inner setting: Readiness for implementation—available resources IV.…”
Section: Introductionmentioning
confidence: 99%